2014
DOI: 10.1007/s12311-014-0601-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Links Between Cerebellum and Dystonia

Abstract: Dystonia is a common movement disorder characterized by sustained muscle contractions. These contractions generate twisting and repetitive movements or typical abnormal postures, often exacerbated by voluntary movement. Dystonia can affect almost all the voluntary muscles. For several decades, the discussion on the pathogenesis has been focused on basal ganglia circuits, especially striatal networks. So far, although dystonia has been observed in some forms of ataxia such as dominant ataxias, the link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
(37 reference statements)
1
14
0
Order By: Relevance
“…These findings were reminiscent of our results in which we found that mouse cerebellum and motor cortex anatomy was abnormal. These results lead us to suspect that the motor defect of ZIKV-infected mice was at least partly, if not totally, a result of abnormal cerebella and motor cortices, considering the strong correlation between motor disorders and cerebellar defects (Malone et al, 2014). In Brazil, it is estimated that > 1800 babies were born with microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were reminiscent of our results in which we found that mouse cerebellum and motor cortex anatomy was abnormal. These results lead us to suspect that the motor defect of ZIKV-infected mice was at least partly, if not totally, a result of abnormal cerebella and motor cortices, considering the strong correlation between motor disorders and cerebellar defects (Malone et al, 2014). In Brazil, it is estimated that > 1800 babies were born with microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…16 While studies with animal models clearly provide additional evidence that disturbances to the basal ganglia can induce dystonia, 15 they also provide evidence that disturbances to the cerebellum can cause dystonia. 15,18 In a network model, dystonia could result from dysfunction affecting one or more of the brain regions within the network or from abnormal communication between brain regions within the network. As a role for the cerebellum and associated thalamocortical circuits is increasingly recognized, one possibility is that a dysfunctional interaction between basal ganglia and cerebellar networks causes dystonia (figure).…”
Section: Dystonia As a Network Disordermentioning
confidence: 99%
“…The pathophysiology of focal dystonia is still not entirely clear. Although dystonia is considered a basal ganglia disorder (Bhatia and Marsden 1994; DeLong and Wichmann 2007), recent studies indicate that the cerebellum may also be involved in this condition (Sadnicka et al, 2012; Prudente et al, 2014; Malone et al, 2014). …”
Section: Introductionmentioning
confidence: 99%